Structural reversal of disc cupping measured in Bruch’s membrane opening-based OCT morphometry after PRESERFLO microshunt implantation for open-angle glaucoma - Jan Niklas Lüke; Constantin Popp; Caroline Gietzelt; Florian Steinberg; Vincent Lüke; Alexandra Lappa; Thomas Dietlein; Philip Enders (BMC Ophthalmology)
Abstract Background/ Aims To analyze the longitudinal change in Bruch’s membrane opening minimal rim width (BMO-MRW) and peripapillary retinal nerve fiber layer (pRNFL) thickness using optical coherence tomography (OCT) after implantation of a PRESERFLO® microshunt for surgical glaucoma management in adult glaucoma patients. Methods Retrospective data analysis of 59 eyes of 59 participants undergoing implantation of a PRESERFLO microshunt between 2019 and 2022 at a tertiary center for glaucoma management. Surgical management included primary temporary occlusion of the glaucoma shunt to prevent early hypotony. Pre- and post-operative OCT examinations of the optic nerve head (ONH) and intraocular pressure (IOP) were assessed. Longitudinal change in morphometric spectral domain OCT parameters of the ONH was correlated to change in IOP. Results BMO-MRW increased significantly between baseline (BL) and follow-up (FU) within the first three months after surgery (BL = 171.15 ± 66.80 μm; FU = 180.78 ± 70.394 μm; p = 0.034). For the same postoperative period, the mean preoperative IOP of 24.97 ± 7.22mmHg was lowered after surgery to 13.70 ± 5.09 mmHg. Eighteen months after surgery, there was no significant change in BMO-MRW compared to baseline (BL = 169.83 ± 52.69 μm; FU = 164.98 ± 55.85 μm; p = 0.271), while mean IOP was 13.08 ± 4.48 mmHg. A decrease in IOP correlated significantly with a change in BMO-MRW (r = 0.453, p < 0.05) three months after surgery. Peripapillary RNFL thickness was unchanged in follow-up after three months (p > 0.16) and significantly decreased in later follow-up (p = 0.009). Conclusion PRESERFLO® microshunt implantation with primary temporary occlusion leads to a significant transient increase in BMO-MRW. This phenomenon is also known as structural reversal of disc cupping (SRDC). The effect seems to be less pronounced and of shorter duration when compared to previous data after trabeculectomy with comparable pre- and postoperative IOP levels.